(untitled) (Perner’s Contacts, 2022)
The main objective of this paper is to conduct an analysis of image pre-processing methods and to state individual authors and publications dealing with them. In order to obtain a systematic review, a methodology of relevant sources‘ searching is proposed in the article. The methods of image pre-processing precede the automatic detection of road users. Thank to suitably chosen image pre-processing process is the automatic detection more accurate and faster as well as consequent classification of the detected objects and their tracking. Suitable image pre-processing is used by the standard background subtraction method and by modern methods working on the principle of neural networks like CNN, YOLO, SSD etc. The content of this article is a review of individual most commonly used pre-processing methods and publications, where individual authors use them to prepare frames prior to various automatic detection methods. An evaluation of results follows and in the conclusion ways for further research are proposed based on the analysis.